A Revised Classification of von Willebrand Disease - Sadler, J Evan (Thrombosis and Haemostasis, 1994)
A simplified phenotypic classification of von Willebrand disease is proposed that is based on differences in pathophysiology. Quantitative defects arc divided into partial deficiency (type 1) and severe deficiency (type 3). Qualitative defects (type 2) are divided into four subcategories. Type 2A refers to variants with decreased platelet-dependent function associated with the loss of high-molecular weight VWF multimers. Type 2B refers to variants with increased affinity for platelet glycoprotein lb. Type 2M refers to qualitatively abnormal variants with decreased platelet-dependent function not associated with the loss of high-molecular weight multimers. Type 2N refers to variants with decreased affinity for factor VIII. When recognized, mixed phenotypes caused by compound heterozygosity are indicated by separate classification of each allele. Standard amino acid and nucleotide numbering schemes are recommended for the description of mutations.